Composite magnetic sheet
By using composite magnetic sheets made of metal magnetic powder with high saturation magnetization and adhesive, adjusting the thickness and aspect ratio of the powder, the problem of difficulty in dealing with electromagnetic noise in higher frequency bands is solved in the prior art, and the noise absorption effect at higher frequency is achieved.
Patent Information
- Application Number
- CN202380055658.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively deal with electromagnetic noise in higher frequency bands, especially in communication devices and systems.
A composite magnetic sheet containing metal magnetic powder and binder with high saturation magnetization is used to adjust the thickness and aspect ratio of the powder, so that the peak frequency on the high frequency side appears on the higher frequency side, thereby absorbing higher frequency electromagnetic noise.
It realizes magnetic resonance in higher frequency bands, effectively absorbs electromagnetic noise at higher frequencies, and improves the noise suppression effect.
Smart Images

Figure CN119547164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite magnetic sheet. Background Art
[0002] Composite magnetic sheets are also called noise suppression sheets. An example of a noise suppression sheet is described in Patent Document 1. The near-field noise suppression sheet described in Patent Document 1 is configured to process magnetic field noise in a wide frequency band of MHz to GHz. In detail, the near-field noise suppression sheet of Patent Document 1 includes a substrate composed of an organic substance, a flat alloy powder supported in the substrate, and a flame retardant dispersed in the substrate.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent No. 6633037. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] With the development of communication devices and communication systems in recent years, there is a demand for handling electromagnetic noise in a higher frequency band. Therefore, an object of the present invention is to provide a composite magnetic sheet that handles electromagnetic noise in a higher frequency band.
[0008] Solutions for solving problems
[0009] One aspect of the present invention provides a composite magnetic sheet as a first composite magnetic sheet, which comprises a metal magnetic powder and a binder, wherein the saturation magnetization of the composite magnetic sheet is greater than 0.73 T and less than 1.20 T, the average thickness of the metal magnetic powder is greater than 0.1 μm and less than 3.0 μm, and the average aspect ratio of the metal magnetic powder is greater than 2 and less than 200.
[0010] Effects of the Invention
[0011] The composite magnetic sheet of the present invention has high saturation magnetization, and the alloy powder contained in the composite magnetic sheet has a thin thickness and a low aspect ratio, so that the composite magnetic sheet can exhibit magnetic resonance in a higher frequency band and absorb electromagnetic noise of a higher frequency.
[0012] By referring to the attached Figure 1 The objectives of the present invention will be properly understood while studying the following description of the best mode of implementation and a more complete understanding of its structure will be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a graph showing a typical example of the spectrum of the imaginary part of the complex relative magnetic permeability of a single particle of the metal magnetic powder used in the composite magnetic sheet.
[0014] Figure 2 It is a diagram for explaining the magnetization state of flat particles.
[0015] Figure 3 This is a flow chart for explaining a method for producing a composite magnetic sheet.
[0016] Figure 4 This is a graph showing the relationship between the particle size of the nanocrystal powder of Comparative Example 1 and the number of pulverization treatments.
[0017] Figure 5 This is a graph showing the relationship between the particle size of the compound powder of Example 1 and the number of pulverization treatments.
[0018] Figure 6 It is a graph showing the magnetization curve of the nanocrystal powder (Comparative Example 1) and the magnetization curve of the compound powder (Example 1).
[0019] Figure 7 This is a diagram showing an X-ray diffraction pattern of a nanocrystal powder that has not been subjected to a grinding treatment (Comparative Example 1).
[0020] Figure 8 This is a diagram showing an X-ray diffraction pattern of a compound powder (Example 1) that has not been subjected to a pulverization treatment.
[0021] Fig. 9 This is a diagram showing an X-ray diffraction pattern of the pulverized nanocrystal powder (Comparative Example 1).
[0022] Fig.10 This is a diagram showing an X-ray diffraction pattern of the pulverized compound powder (Example 1).
[0023] Fig.11 It is a graph showing the complex relative magnetic permeability spectrum of the composite magnetic sheet produced using the nanocrystalline powder (Comparative Example 1) and the complex relative magnetic permeability spectrum of the composite magnetic sheet produced using the compound powder (Example 1).
[0024] Fig.12 It is a graph showing the complex relative magnetic permeability spectrum of the composite magnetic sheet produced using the FeSiCr alloy powder (Comparative Example 2) and the complex relative magnetic permeability spectrum of the composite magnetic sheet produced using the compound powder (Example 1).
[0025] Fig.13 This is a graph for explaining the half-peak width in the complex relative magnetic permeability spectrum (imaginary part).
[0026] Fig.14 This is a graph for explaining the half-peak width of the complex relative magnetic permeability spectrum (imaginary part) of the composite magnetic sheet produced using the compound powder of Example 1.
[0027] Fig.15 is the saturation magnetization μ0M s This is a graph showing the relationship between the particle shape of the metal magnetic powder of 1.70 T and the peak frequency fc of the complex relative magnetic permeability spectrum (imaginary part).
[0028] Fig.16 is the saturation magnetization μ0M s This is a graph showing the relationship between the particle shape of the metal magnetic powder of 1.80 T and the peak frequency fc of the complex relative magnetic permeability spectrum (imaginary part).
[0029] Fig.17 is the saturation magnetization μ0M s The graph is a graph showing the relationship between the particle shape of the metal magnetic powder of 1.90 T and the peak frequency fc of the complex relative magnetic permeability spectrum (imaginary part).
[0030] Fig.18 is the saturation magnetization μ0M s This is a graph showing the relationship between the particle shape of the metal magnetic powder at 2.15 T and the peak frequency fc of the complex relative magnetic permeability spectrum (imaginary part).
[0031] Fig.19 is the saturation magnetization μ0M s The graph is a graph showing the relationship between the particle shape of the metal magnetic powder of 2.35 T and the peak frequency fc of the complex relative magnetic permeability spectrum (imaginary part). DETAILED DESCRIPTION
[0032] The present invention can be implemented in various ways and in various forms. As an example, the specific embodiment shown in the accompanying drawings is described in detail below. The drawings and embodiments are not limited to the specific embodiments disclosed herein, and the objects thereof include all modifications, equivalents and alternatives made within the scope clearly indicated in the attached claims.
[0033] A composite magnetic sheet according to one embodiment of the present invention includes at least metal magnetic powder and a binder. r The shape of the spectrum of ″ depends on the imaginary part μ of the relative magnetic permeability of the metal magnetic powder contained in the composite magnetic sheet. r ”. The imaginary part of the relative magnetic permeability of a single particle of metal magnetic powder μ r The typical spectrum of Figure 1 By making the high-frequency peak of the two peaks, that is, the high-frequency peak frequency fc, appear at a higher frequency side, the composite magnetic sheet can suppress or absorb electromagnetic noise in a higher frequency band.
[0034] like Figure 2As shown in FIG. 1 , the magnetization state of the flat particles without an external magnetic field is closed at the periphery of the flat particles. At this time, the natural frequency fc of the magnetic resonance caused by the precession of each magnetization is as shown in Mathematical Formula 1. The saturation magnetization intensity here excludes the vacuum permeability μ0 and is given by M s (Unit: A / m)
[0035] [Mathematical formula 1]
[0036]
[0037] Here, γ: magnetogyroscopic ratio, M s : Saturation magnetization, N ρ Demagnetization coefficient of flat particles in the radial direction, N z : Demagnetization coefficient of flat particles in the vertical direction, N ρ +N z =1.
[0038] As can be understood from Mathematical Formula 1, as a method for making the high-frequency side peak frequency (natural frequency) fc appear on the high-frequency side, there are: increasing the saturation magnetization μ0M of the metal magnetic powder s Method for increasing the demagnetization coefficient of metal magnetic powder. Saturation magnetization μ0M s Depends on the composition of the metal magnetic powder. In addition, the demagnetization coefficient depends on the shape of the metal magnetic powder. The present invention uses a magnetic material with a higher saturation magnetization intensity μ0M s The metal magnetic powder is used as the metal magnetic powder, and the thickness and aspect ratio of the metal magnetic powder are set in appropriate ranges, so that the high-frequency side peak frequency fc appears on the higher frequency side.
[0039] First, refer to Figure 3 The method for producing the composite magnetic sheet of the present embodiment will be briefly described. However, the method for producing the composite magnetic sheet of the present invention is not limited to the present embodiment, and various modifications can be made.
[0040] First, as a starting material of metal magnetic powder, an alloy powder obtained by atomization method or the like is prepared. In addition, the alloy powder has ferromagnetism. Next, the alloy powder is heat-treated (step S201). Next, the heat-treated alloy powder is ground, i.e., pulverized, to obtain a flat powder (step S202). Then, the flat powder is mixed with a resin as a binder (step S203) to obtain a mixture. Next, the mixture is formed into a film on a substrate (step S204), and dried to obtain a preparatory sheet. One or more preparatory sheets are molded to obtain a composite magnetic sheet (step S205).
[0041] As can be understood from the above description, in this embodiment, the metal magnetic powder contained in the composite magnetic sheet is a flat powder. In other words, in this embodiment, the metal magnetic powder has a roughly disk shape. This shape takes into account the skin effect or skin depth. In such a metal magnetic powder having a roughly disk shape, the high-frequency side peak frequency fc depends on the main radial demagnetization coefficient N ρ Therefore, in order to increase the high-frequency side peak frequency fc, it is only necessary to increase the demagnetization coefficient N ρ In addition, in order to increase the demagnetization coefficient N of the metal magnetic powder ρ , as long as its aspect ratio is reduced. However, due to the relationship with the skin effect, increasing the thickness t of the metal magnetic powder is not preferred. Therefore, it is desired to reduce the aspect ratio without increasing the thickness t of the metal magnetic powder.
[0042] Hereinafter, the metal magnetic powder used for the composite magnetic sheet of the present embodiment will be described using Examples and Comparative Examples.
[0043] Preparation of Fe by atomization 84.3 B 6.0 Si 0.5 P 8.5 Cu 0.7 The alloy powder of the composition represented is heat-treated in a manner that does not cause the precipitation of compounds (step S201), so that nanocrystals are precipitated, and nanocrystal powder is obtained (hereinafter referred to as Comparative Example 1). In addition, the alloy powder obtained in the same manner as Comparative Example 1 is heat-treated to precipitate compounds, and compound powder is obtained (hereinafter referred to as Example 1). In addition, in the present embodiment, "nanocrystalline powder" refers to a powder whose crystalline phase is composed only of crystals having a crystal structure with a body-centered cubic lattice (BCC: Body Centered Cubic) structure. In addition, in the present embodiment, "compound powder" refers to a powder containing crystals whose crystalline phase has a crystal structure other than the BCC structure. Both "nanocrystalline powder" and "compound powder" contain amorphous phases.
[0044] The magnetization curves of Comparative Example 1 and Example 1 were measured. The results are shown in Figure 6 and Table 1.
[0045] [Table 1]
[0046]
[0047] Depend on Figure 6 As can be understood from Table 1, the magnetization curve of Comparative Example 1 and the magnetization curve of Example 1 show that Example 1 is less magnetizable and has a larger magnetic anisotropy than Comparative Example 1. s , there is no difference between Comparative Example 1 and Example 1.
[0048] The grinding process (step S202) was repeated for Comparative Example 1 and Example 1 to study the particle size. Figure 4 As shown in FIG. 1 , even if the grinding process (step S202) is repeated for Comparative Example 1, the particle size D hardly changes. In contrast, when the grinding process is repeated for Example 1, as shown in FIG. Figure 5 As shown, its particle size D will gradually decrease. However, for the compound powder, when a certain degree of grinding is performed, its particle size D hardly changes. Before the grinding process, the particle size D of the nanocrystalline powder is roughly the same as the particle size D of the compound powder. After the grinding process, the particle size D of the compound powder becomes about 1 / 3 of the particle size D of the nanocrystalline powder. Thus, in Comparative Example 1, a powder with an average thickness of 1 μm and an average aspect ratio of 300 is obtained, and in Example 1, a powder with an average thickness of 1 μm and an average aspect ratio of 11 is obtained. In this way, when the compound is precipitated during the heat treatment (step S201), the particle size can be reduced by the subsequent grinding process (step S202). In other words, compared with the nanocrystalline powder, the compound powder can reduce the diameter of the flat powder. This is because the compound powder is more brittle than the nanocrystalline powder. Moreover, since the flat powder with a small particle size has a lower aspect ratio when the thickness is the same, it can be expected to have a larger demagnetization coefficient N. ρ .
[0049] X-ray diffraction was performed on Comparative Example 1 and Example 1 before and after the grinding process. The Bragg-Brentano method was used as the X-ray diffraction method, and Cu was used as its radiation source. The results are shown in Figure 7 to Figure 10 .
[0050] When reference Figure 7 The X-ray diffraction pattern of Comparative Example 1 before the grinding process has multiple significant peaks (with Miller indexes). The diffraction angles obtained by these peaks are consistent with the diffraction angles obtained by the peaks of the diffraction pattern of α-Fe. In addition, the X-ray diffraction pattern was measured by the focusing method (Bragg-Brentano) using Cu as the radiation source. Figure 8 to Figure 10 Same.
[0051] When reference Figure 8 When, the X-ray diffraction pattern of Example 1 before the grinding process has multiple significant peaks (with Miller indexes), and also has multiple small peaks (represented by ▽). The diffraction angle obtained by the significant peak is consistent with the diffraction angle obtained by the peak of the diffraction pattern of α-Fe. On the other hand, the small peak comes from the compound. Thus, nanocrystalline powder and compound powder can be identified from each other by comparing their X-ray diffraction patterns.
[0052] When reference Fig. 9 When the X-ray diffraction pattern of the pulverized comparative example 1 is Figure 7 The diffraction intensity is lower than that of Figure 7 Similarly, Fig.10 In the X-ray diffraction pattern of Example 1 after the grinding process shown in FIG. 1 , the diffraction angle of the peak is also similar to Figure 8 Therefore, the ground comparative example 1 and the ground example 1 can be identified from each other by comparing their X-ray diffraction patterns. In addition, the length direction of the flat particle cross section of these flat powders is in-plane oriented, and when the in-plane is set to an angle θ=0°, the incident X-ray scan is 10°≤θ≤60°.
[0053] A composite magnetic sheet was prepared using Comparative Example 1, and its relative magnetic permeability was measured. In addition, a composite magnetic sheet was prepared using Example 1, and its relative magnetic permeability was measured. The measurement results are shown in Fig.11 and Table 2. In addition, the saturation magnetization μ0 M of the composite magnetic sheet of Comparative Example 1 is s is 0.816T, and the saturation magnetization μ0M of the composite magnetic sheet of Example 1 is s The relative magnetic permeability of the composite magnetic sheet made of a FeSiCr alloy crystal powder (hereinafter referred to as Comparative Example 2) was measured, and the results are shown together with the results of the composite sheet made of Example 1. Fig.12 and Table 3. In addition, the average aspect ratio of the crystal powder of Comparative Example 2 is 1, and the saturation magnetization μ0 M of the composite magnetic sheet of Comparative Example 2 is s It is 0.938T.
[0054] [Table 2]
[0055]
[0056] [Table 3]
[0057]
[0058] Depend on Fig.11 As can be understood from Table 2, the imaginary part μ of the relative magnetic permeability of the composite magnetic sheet of Comparative Example 1 is r ″ shows a high value at frequencies above several tens of MHz. Therefore, the composite magnetic sheet of Comparative Example 1 is suitable for suppressing high-frequency noise above several tens of MHz. In addition, the imaginary part μ of the relative permeability of the composite magnetic sheet of Comparative Example 1 is r "There is a high-frequency side peak frequency fc near 1.5 GHz. However, although the composite magnetic sheet of Comparative Example 1 has the effect of suppressing noise in the high frequency band of several tens of MHz, it may also attenuate the desired signal in the low frequency band of 20 MHz to 200 MHz.
[0059] On the other hand, by Fig.11 As can be understood from Table 2, the imaginary part μ of the relative permeability of the composite magnetic sheet of Example 1 is r "There is a high-frequency side peak frequency fc near 6 GHz. At frequencies higher than the high-frequency side peak frequency fc, the imaginary part μ of the relative permeability of the composite magnetic sheet of Example 1 is r ″Has the same imaginary part μ of the relative magnetic permeability as that of the composite magnetic sheet of Comparative Example 1 r Therefore, the composite magnetic sheet of Example 1 is suitable for suppressing noise in a relatively high frequency band (6 GHz ~), and can accurately absorb electromagnetic noise in a high frequency band without hindering the desired signal in a low frequency band of 20 MHz to 200 MHz.
[0060] Depend on Fig.12 As can be understood from Table 3, the imaginary part μ of the relative permeability of the composite magnetic sheet of Comparative Example 2 is r "There is a high-frequency side peak frequency fc near 3 GHz. At frequencies higher than the high-frequency side peak frequency fc, the imaginary part μ of the relative permeability of the composite magnetic sheet of Comparative Example 2 is r ” slowly decreases with the increase of frequency. Moreover, when the frequency is greater than 10 GHz, the imaginary part μ of the relative permeability of the composite magnetic sheet of Comparative Example 2 r "Having the same imaginary part μ of the relative magnetic permeability as that of the composite magnetic sheet of Example 1 r Therefore, the composite magnetic sheet of Comparative Example 2 is suitable for noise suppression in the same high frequency band (10 GHz ~) as Example 1. However, since the composite magnetic sheet of Comparative Example 2 has the effect of suppressing noise in the high frequency band of several tens of MHz ~, it is also possible to attenuate the required signal in a wide range.
[0061] Here, we study the suppression of noise in a higher desired frequency band, such as the 28 GHz band. Currently, there is no metal magnetic powder that can make the high-frequency side peak frequency fc of the imaginary part of the relative permeability of the composite magnetic sheet reach more than 28 GHz. Therefore, as a frequency range where a sufficient noise suppression effect can be obtained, the concept of half-peak width is introduced. That is, considering the imaginary part μ of the relative permeability of the composite magnetic sheet r In the frequency characteristics of ", the frequency that reaches a value equal to 1 / 2 of the high-frequency side peak is set to a desired frequency, for example, 28 GHz or more.
[0062] like Fig.13 As shown in the figure, it is assumed that the imaginary part μ of the relative permeability of the composite magnetic sheet is r The frequency characteristic of "is a single-peak magnetic resonance. In addition, it is assumed that its peak frequency is equivalent to the high-frequency side peak frequency fc of the imaginary part of the relative permeability of the composite magnetic sheet. Fig.13 In the case of fc=f0, the imaginary part of the relative permeability μ r The value of ″ is μr ″=μ r ″ res In addition, the imaginary part of the relative permeability μ r The value of ″ is μ r ″=μ r ″ res / 2 is set to f1, f2. At this time, the half-peak width Δf (=f2-f1) can be expressed by Δf=2αf0. Here, α is the damping factor, and empirically takes a value of 0.5 to 1.0. When Δf is used to represent the frequency f2 (hereinafter referred to as the half-value frequency f2), f2=f0+Δf / 2. The half-value frequency f2 is set to the desired frequency, for example, above 28GHz.
[0063] In the case of the composite magnetic sheet of Example 1, the high-frequency side peak frequency fc is fc=6 GHz, so assuming α=1, f2=f0+Δf / 2=12 GHz. Fig.14 It can be understood that the above assumption is consistent with the actual measurement results. Table 4 shows the results of the half-value frequency f2 obtained when α=0.5 and α=1.0 for various cases where the high-frequency side peak frequency fc is 1 to 30.
[0064] [Table 4]
[0065]
[0066] As can be understood from Table 4, when α=1, above fc=5GHz, 10GHz noise can be processed. Also, when α=1, above fc=15GHz, 28GHz noise can be processed. On the other hand, when α=0.5, above fc=10GHz, 15GHz noise can be processed. Also, when α=0.5, above fc=20GHz, 28GHz noise can be processed.
[0067] Next, the imaginary part μ of the relative magnetic permeability of the metal magnetic powder is r The relationship between the high-frequency side peak frequency fc of ″ and the thickness and aspect ratio of the metal magnetic powder is explained.
[0068] Depend on Figure 15 to Figure 19 It can be understood from the various figures that when the thickness t of the metal magnetic powder is constant, the smaller the diameter D of the metal magnetic powder is, the greater the imaginary part μ of the relative magnetic permeability of the metal magnetic powder is. r ″, the higher the high-frequency side peak frequency fc. In addition, when the diameter D of the metal magnetic powder is constant, the thicker the thickness t of the metal magnetic powder, the higher the high-frequency side peak frequency fc. As such, it can be considered that the smaller the aspect ratio of the metal magnetic powder, the higher the high-frequency side peak frequency fc.
[0069] In addition, by Figure 15 to Figure 19It can be understood from the figure that when the aspect ratio of the metal magnetic powder is constant, the saturation magnetization intensity μ0M s The larger it is, the higher the high-frequency side peak frequency fc is.
[0070] exist Figure 15 to Figure 19 In each figure, if the high-frequency side peak frequency fc is within the range represented by gray tone, the half-value frequency f2 reaches 10GHz (α=0.5) to 30GHz (α=1.0). Therefore, although it also depends on the value of α, if the high-frequency side peak frequency fc is 15GHz or more, the composite magnetic sheet using metal magnetic powder can handle 28GHz noise.
[0071] In this embodiment, the metal magnetic powder uses Fe as the main raw material. By using Fe as the main raw material, a high saturation magnetization can be achieved. For example, the metal magnetic powder can be pure iron (α-Fe). The saturation magnetization of pure iron is μ0M s 2.15 T. In addition, the metal magnetic powder may be permendur (Fe-49Co-2V). The saturation magnetization of permendur is μ0 M s It is 2.35T.
[0072] In addition, in the present embodiment, the metal magnetic powder may be an alloy composition composed of Fe as a main component of the main raw material and inevitable impurities. Here, the main component of the metal magnetic powder is a composition formula Fe a M w Cu z The metal alloy represented by. M is a combination of at least two or more of B, Si, P and C. In particular, M preferably contains B and P. This is because P contributes to the precipitation of compounds and B contributes to the embrittlement of metal magnetic powders. In the above composition formula, a=100-wz, 0<w≤25at%, 0≤z≤2at%. Such an alloy composition exhibits higher brittleness than pure iron and Perminde alloy by causing the compounds to precipitate. Therefore, the alloy composition can easily reduce its particle size and can reduce the aspect ratio without increasing the thickness t. As a result, a high relative permeability imaginary part μ can be achieved in a frequency band higher than the high-frequency side peak frequency fc, for example, a frequency band above 10 GHz. r ” value.
[0073] In this embodiment, the main component of the metal magnetic powder can be composed of the composition formula Fe a B b Si c P x C y Cu zIndicated. Here, 80≤a≤95at%, 1≤b≤20at%, 0≤c≤10at%, 1≤x≤20at%, 0≤y≤5at%, 0.4≤z≤1.4at%. Because a high saturation magnetization can be obtained, Fe is preferably 80at% or more, and because it contributes to the embrittlement of the metal magnetic powder and the reduction of the melting point, Fe is preferably 95at% or less. Because it contributes to the embrittlement of the metal magnetic powder, B is preferably 1at% or more, and because the reduction of the saturation magnetization can be suppressed, B is preferably 20at% or less. Because the reduction of the saturation magnetization can be suppressed, Si is preferably 10at% or less. Because it contributes to the embrittlement of the metal magnetic powder, P is preferably 1at% or more, and because the reduction of the saturation magnetization can be suppressed, P is preferably 20at% or less. Because the reduction of the saturation magnetization and the deterioration of the magnetic properties can be suppressed, C is preferably 5at% or less. Cu contributes to the embrittlement of the metal magnetic powder and can precipitate uniform nanocrystals, thereby contributing to the improvement of the saturation magnetization, so Cu is preferably 0.4at% or more, and Cu is preferably 1.4at% or less because it can suppress the deterioration of magnetic properties. By using the metal magnetic powder having the above composition, the saturation magnetization of the metal magnetic powder can be obtained to be 1.70T or more.
[0074] In this embodiment, less than 3 at% of Fe in the main component of the metal magnetic powder can be replaced with one or more elements selected from Al, Ti, Mn, S, O, N, Ca, V, Zr, Hf, Nb, Ta, Mo, W, Cr, Co, Ni, Ag, Zn, Ga, Ge, In, Sn, As, Sb, Bi, Y and rare earth elements. Alternatively, in this embodiment, less than 40 at% of Fe in the main component of the metal magnetic powder can be replaced with at least one element selected from Co and Ni. Co and Ni are elements that bear magnetism and contribute to improving the saturation magnetization.
[0075] In this embodiment, the crystal structure of the metal magnetic powder may not be a single crystal structure. In other words, the metal magnetic powder of this embodiment may be a mixed crystal containing two or more crystal structures. In this embodiment, one of the crystal structures is a body-centered cubic lattice structure containing Fe. In addition, the metal magnetic powder of this embodiment may also contain an amorphous phase.
[0076] In this embodiment, the saturation magnetization of the metal magnetic powder is μ0 M s It is 1.70 T or more and 2.35 T or less. In addition, the coercive force of the metal magnetic powder is 1 mT or more. This is to achieve the desired noise suppression effect in a high frequency, for example, in the 28 GHz band.
[0077] In this embodiment, by using a saturation magnetization μ0 M having a high saturation magnetization sThe composite magnetic sheet can be made by using metal magnetic powder and high molecular weight acrylic polymer (molecular weight Mw ≥ 800000) as a binder to obtain a high saturation magnetization intensity μ0M s In addition, in this embodiment, the density of the composite magnetic sheet can be 3.7 g / cm 3 In other words, the composite magnetic sheet of this embodiment can achieve a high saturation magnetization μ0 M even if the density is low. s .
[0078] In this embodiment, the saturation magnetization of the composite magnetic sheet is μ0 M s For example, the saturation magnetization μ0 M of a composite magnetic sheet containing 43 vol.% of a metal magnetic powder having a saturation magnetization of 1.70 T is s The saturation magnetization μ0 M of the composite magnetic sheet containing 51 vol.% of the metal magnetic powder having a saturation magnetization of 2.35 T is 0.73 T. s 1.20 T. The saturation magnetization of the composite magnetic sheet is μ0 M s It is preferably 0.73 T or more and 0.97 T or less. This is because the imaginary part μ of the relative magnetic permeability of the metal magnetic powder in the high frequency band is increased. r ″, even if some saturation magnetization μ0M is sacrificed s , it is also effective to reduce the aspect ratio. For example, a 51 vol.% alloy containing 90 at.% Fe and a saturation magnetization of μ0 M s The saturation magnetization of the metal flakes with a metal magnetic powder of 1.9 T is 0.97 T.
[0079] In order to achieve the above saturation magnetization μ0M s The metal magnetic powder of this embodiment is ground so that its average thickness is greater than 0.1 μm and less than 3.0 μm, and its average aspect ratio is greater than 2 and less than 200. The average thickness of the metal magnetic powder is preferably greater than 0.1 μm and less than 1.0 μm, and the average aspect ratio is preferably greater than 2 and less than 20. This is because although the aspect ratio is preferably small, when the aspect ratio is less than 2, it is not easy to orient it in the composite magnetic sheet. In addition, when the aspect ratio is greater than 200, the desired characteristics cannot be obtained. When the aspect ratio is less than 20, at a frequency of 28 GHz, the imaginary part of the relative permeability μ r ″ becomes a value greater than 1 / 2 of the high-frequency side peak value.
[0080] As described above, the composite magnetic sheet of the present embodiment is formed by using a magnetic sheet having a higher saturation magnetization μ0 M. sBy using metal magnetic powder as the metal magnetic powder and setting the thickness and aspect ratio of the metal magnetic powder within appropriate ranges, noise in a higher frequency, such as the 28 GHz band, can be suppressed.
[0081] As mentioned above, although embodiment of the present invention was mentioned and described, this invention is not limited to the said embodiment, Various deformation|transformation and change are possible within the range which does not deviate from the summary of this invention.
[0082] For example, the metal magnetic powder may have an oxide layer or a nitride layer on its surface. This is to increase the resistance. By increasing the resistance, the noise suppression sheet can also be used in the higher voltage part of the electronic equipment. In other words, the use of the noise suppression sheet can be expanded.
[0083] The present invention is based on Japanese Patent Application No. 2022-120978 filed with the Japan Patent Office on July 28, 2022, the contents of which are incorporated herein by reference as a part of this specification.
[0084] The best mode for carrying out the present invention has been described. However, it is obvious to those skilled in the art that the mode for carrying out the present invention can be modified without departing from the spirit of the present invention. Such mode for carrying out the present invention belongs to the scope of the present invention.
Claims
1. A composite magnetic sheet comprising metal magnetic powder and a binder, The saturation magnetization of the composite magnetic sheet is 0.73 T or more and 1.20 T or less. The average thickness of the metal magnetic powder is 0.1 μm or more and 3.0 μm or less, The metal magnetic powder has an average aspect ratio of 2 or more and 200 or less.
2. The composite magnetic sheet according to claim 1, wherein The density of the composite magnetic sheet is 3.7 g / cm 3 above.
3. The composite magnetic sheet according to claim 1 or 2, wherein: The saturation magnetization is greater than or equal to 0.73T and less than or equal to 0.97T.
4. The composite magnetic sheet according to any one of claims 1 to 3, wherein The average thickness of the composite magnetic sheet is 0.1 μm or more and 1.0 μm or less. The average aspect ratio is 2 or more and 20 or less.
5. The composite magnetic sheet according to any one of claims 1 to 4, wherein The coercive force of the metal magnetic powder is greater than 1 mT.
6. The composite magnetic sheet according to claim 5, wherein: The phase structure of the metal magnetic powder is a mixed crystal of two or more phases including a body-centered cubic lattice crystal structure and other crystal structures, and the body-centered cubic lattice crystal structure contains Fe.
7. The composite magnetic sheet according to claim 6, wherein: The metal magnetic powder is an alloy composition composed of Fe as a main component of a main raw material and inevitable impurities. The main component is composed of the formula Fe a M w Cu z express, M is a combination of at least two of B, Si, P and C, a=100-wz, 0<w≤25at%, 0≤z≤2at%.
8. The composite magnetic sheet according to claim 1, wherein The metal magnetic powder has a saturation magnetization of 1.70 T or more and 2.35 T or less.
9. The composite magnetic sheet according to claim 8, wherein The metal magnetic powder is an alloy composition composed of Fe as a main component of a main raw material and inevitable impurities. The main component is composed of the formula Fe a B b Si c P x C y Cu z It means, 80≤a≤95at%, 1≤b≤20at%, 0≤c≤10at%, 1≤x≤20at%, 0≤y≤5at%, 0.4≤z≤1.4at%.
10. The composite magnetic sheet according to claim 9, wherein The composite magnetic sheet is obtained by replacing less than 3at% of the Fe with one or more elements selected from the group consisting of Al, Ti, Mn, S, O, N, Ca, V, Zr, Hf, Nb, Ta, Mo, W, Cr, Co, Ni, Ag, Zn, Ga, Ge, In, Sn, As, Sb, Bi, Y and rare earth elements.
11. The composite magnetic sheet according to claim 9, wherein The composite magnetic sheet is obtained by replacing 40 at % or less of the Fe with at least one element of Co and Ni.
Citation Information
Patent Citations
Hydraulic control system
JP2022120978A